Carbon rovings as strain sensors for structural health monitoring of engineering materials and structures. (October 2016) - Quadflieg, Till; Stolyarov, Oleg; Gries, Thomas
A prospective method for structural health monitoring of engineering materials and structures is based on embedded strain sensors in the form of electrically conductive carbon rovings. This article presents the results of the application of carbon rovings and the development of flexible textile fabrics based on these rovings for measuring the deformation in engineering materials, including concrete and polymer- and cement-based composites. The possibility of using carbon rovings as a strain sensor is demonstrated via measurements in tensile and four-point bending tests. The experimental setups and methods for measuring the electrical resistance of carbon roving as a function of strain in the roving, concrete, and composites are described. A good correlation has been found between the electrical resistance–strain curve of the carbon roving (used as a calibration curve) and the measurements in the concrete and polymer composites from tensile tests. The difference in the character of the flexural behavior and the electrical signal in the carbon roving cement-based composite, affected by the stitch type and shape of the carbon roving cross section in textile fabric, was found through four-point bending tests.